Dampak Brand Image, Harga, Dan Brand Trust Terhadap Keputusan Menggunakan Paket Umroh (Study Kasus Travel PT. Raya Al-Madinah Karangploso Malang) - Ilmatul Horijah; Nur Hidayati; Satria Putra Utama (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract This study aims to determine and analyze the relationship between Brand Image, Price, and Brand Trust on the Decision to Use the Umroh Package Case Study at Travel PT. Raya Al-Madinah Karangploso Malang. In this study the method used to obtain data is to use a questionnaire. This research was conducted on customers of Travel Raya Al-Madinah, namely at the address Jl. Raya tanjung sari ruko kav 8 kepuharjo Karangploso Malang. East Java Postal Code 65152. Determining the number of samples in this study used "purposive sampling" using a Likert scale and the results obtained were 75 respondents. Hypothesis testing was carried out using Instrument Test, Normality Test, Multiple Linear Regression Test and Coefficient of Determination Test. The results of the Simultaneous Test (Test F) show that the Variables Brand image, price, and brand trust simultaneously influence the decision to use the umroh package (study on Travel PT. Raya Al-Madinah Karangploso Malang). This means that brand image, price, and brand trust can explain the decision to use umroh travel at PT Raya Al-Madinah. Furthermore, the results of the Partial Test (t test) show that the Variables Brand Image (X1), Price (X2), and Brand Trust (X3) have an effect on the decision to use the Umrah package (study at PT. Raya Al-Madinah Karangploso Travel Malang). This means that the higher the decision to use PT Raya Al-Madinah travel. The results of the determination test show that 59.9% of the variation or change in the Purchase Decision can be explained by the variables Price, Product, Promotion and Location. While the remaining 40.1% is influenced by other variables not included in this study. Keywords: Brand Image, Price, Brand Trust, Decision To Use